Impact of lifestyle Intervention on branched‐chain amino acid catabolism and insulin sensitivity in adolescents with obesity. Issue 3 (1st April 2021) - Jachthuber Trub, Catherine; Balikcioglu, Metin; Freemark, Michael; Bain, James; Muehlbauer, Michael; Ilkayeva, Olga; White, Phillip J.; Armstrong, Sarah; Østbye, Truls; Grambow, Steven; Gumus Balikcioglu, Pinar
Introduction: Insulin resistance in adolescents with obesity associates with a sex‐dependent metabolic 'signature' comprising branched‐chain amino acids (BCAAs), glutamate and C3/C5 acylcarnitines (C3/C5), implicating altered flux through BCAA catabolic pathways. Here, we investigated the effects of lifestyle intervention on BCAA catabolism and insulin sensitivity. We hypothesized (1) weight reduction and improved insulin sensitivity associate with enhanced BCAA catabolism; (2) baseline BCAAs and their metabolic by‐products predict changes in weight and insulin sensitivity during lifestyle intervention. Methods: A 33 adolescents with obesity were studied before and after 6 months of lifestyle intervention. Principal component analysis and multiple linear regression models were used to correlate changes in metabolic factors with changes in weight and insulin sensitivity assessed by HOMA‐IR, adiponectin and ratio of triglyceride (TG) to HDL. Baseline metabolic factors were used as explanatory variables in prediction models. Results: Weight reduction was associated with reductions in BCAA, glutamate, and C3/C5 ( p = .002) and increases in urea cycle AA ( p = .029), suggesting an increase in BCAA catabolism. Increases in urea cycle AA during weight reduction were associated with increases in adiponectin, a marker of insulin sensitivity. Markers of insulin resistance (high BCAA, glutamate, and C3/C5 and low urea cycle AA) at baseline predicted increases in metrics of insulin sensitivity (decreased TG/HDL and increased adiponectin) during lifestyle intervention. Conclusions: Weight reduction in adolescents is associated with increases in BCAA catabolism and improvements in insulin sensitivity. Our study underscores the therapeutic potential of manipulating BCAA catabolism to treat obesity‐associated insulin resistance in adolescents and prevent progression to T2D. Abstract : Insulin resistance in adolescents with obesity associates with a sex‐dependent metabolic 'signature' comprising branched‐chain amino acids (BCAAs), glutamate and C3/C5 acylcarnitines (C3/C5), implicating altered flux through BCAA catabolic pathways. Here, we investigated the effects of lifestyle intervention on BCAA catabolism and insulin sensitivity.